Work engagement and individual work performance in the UAE: the mediating role of work-life balance - Alnagbi, Mohamed A.; Aldabbas, Hazem; Gernal, Liza; Elamin, Abdallah M.; Ahmed, Ahmed Z. E. (Frontiers in Sociology, 2025)
This research focuses on how employees balance their engagement with their work and private life, and how this balance affects their performance in the workplace. The study conducted a survey completed by 98 employees from government, private, and non-profit organizations regarding their experiences with engagement, work-life balance, and performance. The findings indicate that workers in UAE-based workplaces are highly engaged in their jobs and perform significantly well. The key results show that work engagement is positively related to work-life balance, which, in turn, positively impacts individual work performance. Additionally, the study demonstrates that work-life balance mediates the relationship between work engagement and individual work performance, helping to explain and facilitate this relationship. This study provides a deeper understanding of work engagement and work-life balance in the UAE and offers insights into how organizations can implement best practices to enhance performance.